2009
DOI: 10.1021/ie8011424
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Hydrogenolysis of Glycerol to Propylene Glycol over Mixed Oxides Derived from a Hydrotalcite-Type Precursor

Abstract: Selective hydrogenolysis of glycerol to propylene glycol was performed using an environmentally friendly hydrotalcite-derived mixed-metal oxide catalyst. The Mg/Al, Zn/Al, Ni/Mg/Al, Ni/Co/Mg/Al, and Cu/Zn/Al mixed-metal oxide catalysts were prepared from their corresponding hydrotalcite precursors having M 2+ /M 3+ compositions over the range of 0.5-3.0. The physicochemical properties of the catalysts were studied by X-ray diffraction (XRD), inductively coupled plasma mass spectrometry (ICP-MS), NH 3 and CO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
1
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 18 publications
7
81
1
11
Order By: Relevance
“…As compared with the result of Meher et al [33], our results showed lower conversions, possibly due to the weak interactions between sulfate ions and the molecular sieves and thus, homogenous catalysis is likely over the solids studied. Also, the dehydration of glycerol suffered from an extensive deactivation phenomena, especially when the reaction was carried out at temperatures as high as 300°C, as shown by the Raman results.…”
Section: Effect Of the Reaction Conditions On The Dehydration Of Glycsupporting
confidence: 50%
See 1 more Smart Citation
“…As compared with the result of Meher et al [33], our results showed lower conversions, possibly due to the weak interactions between sulfate ions and the molecular sieves and thus, homogenous catalysis is likely over the solids studied. Also, the dehydration of glycerol suffered from an extensive deactivation phenomena, especially when the reaction was carried out at temperatures as high as 300°C, as shown by the Raman results.…”
Section: Effect Of the Reaction Conditions On The Dehydration Of Glycsupporting
confidence: 50%
“…It is possible that the reaction conditions studied to produce hydroxyacetone could be milder than that of previous findings with other molecular sieves such as ZSM-5 and oxides [17,[31][32][33], because the reaction would reach the equilibrium. As compared with the result of Meher et al [33], our results showed lower conversions, possibly due to the weak interactions between sulfate ions and the molecular sieves and thus, homogenous catalysis is likely over the solids studied.…”
Section: Effect Of the Reaction Conditions On The Dehydration Of Glycmentioning
confidence: 82%
“…Since water is a by-product in the hydrogenolysis of glycerol, its presence favors the reverse reaction of dehydration, thereby inhibiting hydrogenolysis [45,46]. At a lower water content, 1,2-PDO and ethanol selectivities declined, which may have resulted from the degradation or polymerization of these products [47][48][49]. The decrease in ethanol selectivity may also be caused by an increase in n-propanol production at lower water contents, which competes with the subsequent ethanol production.…”
Section: Effect Of Initial Hydrogen Pressurementioning
confidence: 99%
“…For instance, Cu-Zn-Al oxides, derived from the corresponding hydrotalcite precursor, proved to be highly active and selective in glycerol hydrogenolysis at 473 K, giving a glycerol conversion of 48.0% and a 1,2-propanediol (1,2-PDO) selectivity of 93.9% [18]. We have recently reported that Co/MgO catalysts provided a glycerol conversion of 44.8% and a 1,2-PDO selectivity of 42.2% in glycerol hydrogenolysis at 473 K, but the hydration of MgO to Mg(OH) 2 , under the reaction conditions, caused severe aggregation of the cobalt particles [11].…”
Section: Introductionmentioning
confidence: 99%